Clinical practices for non-neoplastic thymic lesions: Results from a multidisciplinary cohort. (April 2022) - Joubert, Virginie; Chalabreysse, Lara; Gamondes, Delphine; Tronc, François; Maury, Jean-Michel; Girard, Nicolas
Highlights: Non-neoplastic thymic lesions are uncommon findings that corresponds to multiple histological and clinical entities. In 88 operated patients, there were 34 normal thymuses, 29 and 6 lymphoid/non-lymphoid hyperplasias, and 19 thymic cysts. In the 40 non-operated patients, a major driver for the decision of follow-up was the decrease in the lesion signal intensity at MRI. Abstract: Background: Non-neoplastic thymic lesions are uncommon findings that corresponds to multiple histological and clinical entities that may be difficult to differentiate from thymic malignancies. In this study, our main objective was to describe the clinical, imaging and pathological characteristics of non-neoplastic thymic lesions in a large cohort of patients. We also aimed at understanding the key factors that led to a decision to surgically resect those lesions. Methods and Materials: This is an observational, retrospective study. We enrolled both patients with non-neoplastic thymic lesions – normal thymus, thymic lymphoid/non-lymphoid hyperplasia, and thymic cysts - that had been pathologically-confirmed after surgical resection -, and patients with a thymic lesion that was never operated, based on imaging follow-up. Results: A total of 128 patients were included, 88 of whom underwent surgical resection of the lesion (69%), and 40 patients (31%) had follow-up without surgery. Discovery of the lesion was incidental in 69 (54%) cases; thoracic magnetic resonance imaging was performed in 33 (26%) cases, 85% of which showed apparent decrease in the lesion signal intensity in phase opposition at chemical shift sequences. In the 88 operated patients, there were 34 (39%) normal thymuses, 29 (33%) lymphoid hyperplasias, 6 (7%) non-lymphoid thymic hyperplasias, and 19 (22%) thymic cysts. In the 40 non-operated patients, a major driver for the decision of follow-up was the decrease in the lesion signal intensity in phase opposition at chemical shift sequences, observed in 68% of cases; imaging follow-up of these lesions showed sustained regression in the majority of the cases. Conclusions: The management of benign thymic lesions requires multidisciplinary assessment. A strategy that integrates clinical and imaging features, including chemical-shift sequences at magnetic resonance imaging, as well as follow-up, allows a better selection of the patients for surgery.